Zika Virus Infection Knowledge and Communication Preferences Among Women of Reproductive Age in Central Brooklyn, New York: A Thematic Analysis. - Dowling, Russell; Kolokotronis, Sergios-Orestis; Thompson, Azure B. (Journal of Community Health, 2024)
The 2016 outbreak of Zika virus (ZIKV) infected millions and resulted in thousands of infants born with malformations. Though the clusters of severe birth defects resulting from this outbreak have subsided, ZIKV continues to be a concern throughout much of Latin America and the Caribbean. Travel and sexual intercourse remain the dominant transmission risk factors for women of reproductive age and their partners. This is particularly true for communities in Brooklyn, New York, that comprise large immigrant and foreign-born populations. Practitioners of public health understand little about how women at risk for ZIKV are most likely to receive information about the virus or who they trust most to provide that information. In the context of five focus group discussions, this study explored the knowledge and communication preferences of 20 women of reproductive age in Central Brooklyn. Results derived from a thematic analysis suggest that while most women are familiar with mosquitos as ZIKV vectors, knowledge of sexual transmission is considerably lower. Many respondents believe that only women who are pregnant or trying to become pregnant are at risk, and public health agencies, such as the U.S. Centers for Disease Control and Prevention, remain the most trusted sources of information. These findings can support more effective communication about the risks of ZIKV infection and other vector-borne diseases to women in New York City and similar urban communities.